A Study on Emotional Intelligence and Psychological Well Being of Health Care Professionals in the Wake of Covid-19 - Sonia EAPEN; Suneetha RAPAKA (Communications of International Proceedings, 2021)
The unselfish lives of health care professionals sacrificing everything by risking their own lives during Covid 2019 have moved us greatly and this study aims to help them in improving their psychological well being. The psychological well being of the healthcare professional is always at risk whenever there is a pandemic outburst. Being the primary contacts with the affected, the emotional trauma faced by the healthcare professionals is beyond imagination. The only one factor which can help them on this regard is to maintain high levels of emotional intelligence. This study explores the levels of Emotional Intelligence of health care professionals. It also studies the relationship of various components of emotional intelligence with their psychological wellbeing. This study is done with a sample of 110 health care professionals and tried to see if components of emotional intelligence components have an impact on psychological well being. It was found out that the components of Emotional Intelligence – Self Awareness, Self Regulation and Self Motivation are significantly related to the psychological well-being of health care professionals whereas the components – Social Skills and Empathy are not significantly related to the psychological well-being of health care professionals.Also the study throws light on how the psychological well being of health care professionals can be ensured. Connecting to the Divine and serving mankind unselfishly by mastering their emotions truly makes the health care professionals angels in protecting the world.
Keywords: Emotional Intelligence; psychological wellbeing; Health care professionals.